Isotopic and thermochronologic evidence of extremely cold lithosphere associated with a slab flattening in the Central Andes of Argentina. (26th November 2015) - Collo, Gilda; Dávila, Federico M.; Teixeira, Wilson; Nóbile, Julieta C.; Sant′ Anna, Lucy G.; Carter, Andrew
Abstract: We present mineralogic, isotopic and thermochronologic analyses on psammopelitic and tuffaceous levels from the Bermejo and Vinchina basins – both foreland depocentres of the Central Andes of Argentina – that define a low‐temperature regime for the crust akin to a slab shallowing and flattening process. The contents of illite in illite/smectite interstratified (I/S) show a progressive illitization into the deeper parts of both basins. The distribution of I/S is compatible with theoretical simulations and predicted heat flow values of ca . 26 mW m −2 in the 8–3.4 Ma interval for the Vinchina Basin and ca . 42 mW m −2 since 9 Ma for the Bermejo Basin. The latter shows heat flow values that are comparable to those reported by magnetotelluric analysis (36–40 mW m −2 ) in agreement with previously published heat flow calculations along the modern Andean foreland. The Rb–Sr isochrones in psammopelites (<2 μm fractions) show ages between 125 and 165 Ma, whereas the K–Ar ages decrease as the grain size is smaller (136–224 Ma for 1–2 μm, 112–159 Ma for 0.2–1 μm, 76–116 Ma for <0.2 μ and 39.3–42 Ma for <0.1 μm). These ages are significantly older than the sedimentation in the basins ( ca . 16 Ma for the Vinchina Basin; U–Pb age), and can be explained by the presence of a significant amount of detrital components, mainly illite, even in the finer fractions. The preservation of detrital ages is consistent with the shallow diagenesis related to a low‐temperature regime, proposed here for the basins. Younger K–Ar ages (21.3–12 Ma) were obtained for a basal tuffaceous level. Clay mineralogy and R0 ordering in the deepest part of the Vinchina Basin, together with the evolution model of I/S with depth, suggest that the burial temperatures would have not exceeded ca . 100°C in agreement with (U–Th)/He analyses performed on apatite extracted from two tuffaceous units. Thermal indicators from both studied basins confirm the existence of a low‐temperature regime during flat subduction.